An empirical investigation of implementing Lean Six Sigma in Higher Education Institutions. Issue 10 (29th November 2018) - Sunder M., Vijaya; Mahalingam, Sanjay
Abstract : Purpose: The purpose of this paper is to empirically investigate the applicability and implementation of Lean Six Sigma (LSS) in Higher Education Institutions (HEIs). LSS is considered as the most recent service quality practice which has proved its success in manufacturing and service sectors. Though there is plenty of literature available with regard to the application and benefits of LSS in services sectors (like Banking, healthcare, information technology sectors, etc.), there is apparently no evidence in the literature about the implementation of LSS in HEIs. Design/methodology/approach: A five-phased approach is followed. A multiple case-study method is used in this paper to explore this implementation of LSS in two select international University colleges. LSS toolkit comprising of define-measure-analyze-improve-control phases is used for the execution of the projects. Featuring student teams in LSS project management adds novelty to the approach. Findings: The paper empirically validates the application of LSS in HEIs. Further, it highlights the practical challenges and benefits of LSS in the HEI setup. An in-depth empirical analysis of LSS toolkit application, LSS change management and using student teams in LSS project management are the highlights of this paper. The paper concludes that LSS is applicable and could provide positive benefits to HEIs. Research limitations/implications: LSS application in HEIs is perhaps a new research area, which is at its nascence and upcoming in the researchers' community. Hence, this paper would serve as a platform and provide directions for future scholars to ponder on the subject. Practical implications: Since the cases are executed in the real-time setup of HEIs, the paper has several practical implications. First, the academia and practitioners' collaboration in executing projects adds novelty. Second, the involvement of student teams from project selection to execution brings in practical perspectives alongside the academic education. Several other key lessons learned and benefits of LSS in HEI setup are presented as part of the paper. Originality/value: LSS has been successful in the past few decades in the manufacturing and service sectors. However, its application in HEIs was very nascent, and few researchers even doubted its relevancy of application in HEIs. This study illustrates its importance and application to the higher education sector which is a highly responsible area of the service sector, for imbibing quality excellence, serving as an excellent resource for researchers and higher education professionals.